Understanding and mitigating tsunami risk for coastal structures and communities - Park, Sangki, author; Atadero, Rebecca A., advisor; van de Lindt, John W., advisor; Heyliger, Paul R., committee member; Senior, Bolivar A., committee member (Colorado State University. Libraries, 2011)
Tsunamis have attracted the world's attention over the last decade due to their destructive power and the vast areas they can affect. The 2004 Indian Ocean Tsunami, killed more than 200,000 people, and the 2011 Great Tohoku Japan Earthquake and Tsunami, resulted in 15,000 deaths and an estimated US $300B in damage, are recent examples. An improved understanding of tsunamis and their interactive effects on the built environment will significantly reduce loss of life in tsunamis. In addition, it is important to consider both the effect of the earthquake ground motion and the tsunami it creates for certain coastal regions. A numerical model to predict structural behavior of buildings subjected to successive earthquakes and the tsunamis was developed. Collapse fragilities for structures were obtained by subjecting a structure to a suite of earthquake ground motions. After each motion the numerically damaged structural model was subjected to tsunami wave loading as defined by FEMA P646. This approach was then extended to the community level; a methodology to determine the probability of fatalities for a community as a function of the number of vertical evacuation shelters was computed. Such an approach also considered the location and number of vertical evacuation sites as an optimization problem. Both the single structure cases and the community analyses were presented in terms of fragilities as a function of the earthquake intensity level and evacuation time available. It is envisioned that the approach may be extended to any type of structure as they are typically modeled nonlinearly with strength and stiffness degradation. A logical fragility-based, or performance-based, procedure for vertical evacuation for coastal buildings and for whole communities was developed. A mechanism to obtain a reduction in the collapse risk of structure and more critically maximize the survival rate for a community was a major outcome of this dissertation. The proposed tsunami vertical evacuation methodology was intended to provide key information to better understand and mitigate risk caused by earthquakes and tsunamis, thus it is possible to mitigate hazard for a community with only several large vertical evacuation shelters. It is able to provide a framework for a vertical evacuation plan and for the mitigation of collapse risk and fatalities of structures and a community based on a limited amount of information.
Keywords: earthquake; fragilities; nonlinear analysis; reliability assessment; risk analysis; tsunami